Pedagogi Multiliterasi Melalui Pembelajaran Berbasis Fenomena: Model untuk Meningkatkan Perilaku Ekonomi Sirkular di Sekolah Dasar - Mahendra, Arya; Setyowati, Raden Roro Nanik; Rachmadyanti, Putri (Didaktika Dwija Indria, 2026)
This study was motivated by environmental degradation resulting from unsustainable economic practices rooted in a linear economic system (take-make-dispose), alongside the limited provision of circular economy education as a sustainable behavioral framework that integrates real world phenomena with socio-critical reflection in elementary schools. The research aimed to examine the effectiveness of phenomenon-based learning combined with multiliteracy pedagogy in fostering students’ circular economic behavior across knowledge, attitudes, and practices. Employing a pre-experimental one-group pretest-posttest design, the study involved 15 fifth-grade students at SDN Rayung, Tuban Regency. Data were collected through higher-order thinking skills (HOTS)-based multiple-choice tests for knowledge and Likert-scale questionnaires for attitudes and practices. Findings revealed significant improvements in all three dimensions, supported by high N-Gain scores: knowledge (0.84), attitudes (0.83), and practices (0.85). The contextualization of real environmental issues through direct practice effectively enabled students to critically understand sustainable economic behavior. In conclusion, integrating multiliteracy pedagogy into phenomenon-based learning represents an innovative and effective strategy to strengthen cognitive understanding, cultivate critical awareness, and shape sustainable economic practices among elementary school students from an early age.